Comparison of Ketamine and Pentazocine with Fentanyl and Propofol combination for anaesthesia during laparoscopic tubal ligation - Nazir, Ovais; Bhat, Asif Hussain; Yatoo, Hamid; Gupta, Sanjeevni; Misra, Rajesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Laparoscopic tubal ligation have advantages of minimally invasive surgical technique, without risk of major haemorrhage, early postoperative ambulation and alimentation, making it suitable for ambulatory surgery. The choice of aneasthesia for laparoscopic ligation hence should consider the anaesthetic agents with a rapid onset of action and fast recovery time, with minimal problems for intraoperative control of haemodynamic, airway and pain relief as well as take consideration of the safety, quality, efficacy, and utilization of resources available to the given situation. Methods: A total of 100 patients aged from 18 to 45 years who were scheduled to undergo laparoscopic tubal ligation were divided into Group I- Ketamine plus pentazocine group (n=50), Group II- Propofol plus fentanyl group (n=50) and studied for the intraoperative parameters (hemodynamic and respiratory profile), recovery time, postoperative side effects and discharge time. Results: Intraoperatively MAP and HR were consistently higher in group I as compared to group II. Incidence of apnea and need for bag and mask ventilation was significantly more in Group II than in Group I as was the incidence of Bradycardia. Postoperative nausea and vomiting, psychomimetic effects were significantly more in Group I than in Group II. The time to reach modified PADSS ≥9 (discharge time) was significantly longer in group I (140.3±12.82 min than in group II 102.2±9.2 min), P<0.01. Conclusions: Combination of ketamine and pentazocine gives good anaesthetic conditions during procedure with less incidence of airway and haemodynamic complications intraoperatively but more incidence of postoperative side effects like nausea, vomiting, psycomimetic effects, and time to meet discharge criteria, compared to propofol plus fentanyl.